(3GdahGFO GdYHGSjI aj ahGFO abgjI hCUhdjIs - (3GdfLaj, YHGS Hf MSf Hf LYaQ cGTa GdZWGA, J (B1323(3g`s ((3HNW GdeDdas)
(3ChdgG (B:s
(3jbhd GdNGWF GdePfH (B... (3GdYHGS Hf GdMSf(B... (3SCdfj ef dGHO dj ef ELGHJg(B... (3dGQjH aj JMQje bQjH GdEfSGf EdG HfGJ GdYe(B...s
(3BNQgG (B:s
(3Jchf Ydi GdeHGM hjSbW GdJcdja (B... (3gh hGLH Ydi GdeJGLQ Ohf GdCLjQ ef ehVhY GdeSCdIs
(3JHUQI GdYfhGf (B:s
(3GdahGFO GdLYaQjIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf(B: (3L(B2(3, U(B30s
(3eYLe GdeDdajf(B: (3L(B2(3, U(B30s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3abg GdePGgH GdCNQis